Improving Sharia Financial Literature and Inclusion Through Sharia Bank Digital Services - Elsa Tiara; Rifani Raniasati; Hendri Hermawan Adinugraha; Zulaikhah Fitri Nur Ngaisah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The presence of digital banking and financial technology has proven the importance of offering easy, simple, and convenient digital banking services. The development of digital technology has changed the way people use banking services, and Islamic banking is no exception. This can be seen from the increasing number of Islamic bank products offered through digital services to provide the best service for the community. However, in Indonesia itself, the level of literacy and inclusion of Islamic finance in society is still relatively low. The low literacy and inclusion of Islamic finance are indicators that the Islamic financial services industry is still unable to educate the Islamic economy. The purpose of this study is to analyze the strategy of Islamic banks in improving Islamic financial literacy through digital services. The research method used is descriptive qualitative. The data source is secondary data obtained through literature reviews such as books, articles, official websites, and other sources relevant to the research title. The results of this study indicate that Indonesia still has a low level of Islamic financial literacy and inclusion. This causes industry penetration to be less than optimal. Therefore, efforts are needed to develop more competitive Islamic banking products, so as to increase Islamic financial literacy and inclusion in Indonesia. These efforts are by implementing digital account administration banking services, transaction authorization banking digital services, and financial management banking digital services.